Injury of the external genitalia in 10-year-old boy - Kleanthis Anastasiadis; Chrysostomos Kepertis; Dimitrios Sfoungaris; Ioannis Spyridakis (Wolters Kluwer Medknow Publications, 2019)
Degloving injury of penis and scrotum is very rare in child population and requires early reconstructive surgery for good outcomes. We report a 10-year-old boy with complete avulsion of the scrotum and partial of the penis caused by a bicycle chain due to off-road bicycling. The patient has been treated successfully with a single-staged surgery.